1991
DOI: 10.1017/s0021932000019362
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding, birth interval and child mortality in Bangladesh

Abstract: SummaryThe 1975–76 Bangladesh Fertility Survey data show little evidence that breast-feeding is the intermediate factor through which birth intervals influence child survival in Bangladesh. Preceding birth interval, subsequent pregnancy and breast-feeding duration each have an independent influence on early mortality risk. Within a specific interval the risk of dying decreases with increase in duration of breast-feeding, and also with an increase in the time between the index birth and the next pregnancy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A number of previous studies have revealed a significantly higher death rate among non-breast-fed infants compared to those who were breast-fed [30], [31], and failure to attain statistical significance in our study is likely due to the small sample size, as reflected in wide 95% CI. Our observation of indifferent distribution of parental socioeconomic and environmental status among the non-breast-fed and breast-fed infants might also be due to same reason.…”
Section: Discussionmentioning
confidence: 59%
“…A number of previous studies have revealed a significantly higher death rate among non-breast-fed infants compared to those who were breast-fed [30], [31], and failure to attain statistical significance in our study is likely due to the small sample size, as reflected in wide 95% CI. Our observation of indifferent distribution of parental socioeconomic and environmental status among the non-breast-fed and breast-fed infants might also be due to same reason.…”
Section: Discussionmentioning
confidence: 59%
“…The risk of death from diarrhoeal diseases and pneumonia is, respectively, 14 and 4 times higher in bottlefed infants in developing countries compared to infants exclusively breastfed for the first 4-6 months of their lives (14). Breastfeeding exerts its strongest beneficial effect in children aged 1-15 month(s) (18). Since the 1980s, a number of global initiatives have been undertaken to increase the rate of exclusive breastfeeding, including the child-survival resolution by UNICEF, the World Declaration on Children, International Code of WHO for Marketing of Breast Milk Substitutes, the Baby-Friendly Hospital Initiative (BFHI), and the International Conferences on Nutrition.…”
Section: Breastfeedingmentioning
confidence: 99%
“…These factors influence the most proximate determinants of child survival, i.e. breast-feeding and health care practices (Rosenberg, 1989;Majumder, 1991;Kuate Defo, 1997).…”
Section: Introductionmentioning
confidence: 99%